A local instructional theory (LIT) for teaching linear equation through STEM instruction - Siti Maryam Rohimah; Darhim Darhim; Dadang Juandi (Jurnal Elemen, 2022)
Several previous types of research showed that students had obstacles in understanding the concept of linear equations. These obstacles occur because the designed learning cannot facilitate student learning trajectories, thus causing low learning outcomes. This research aimed to design and develop a learning trajectory for the linear equations in one variable material as a systematic set of activities through Science, Technology, Engineering, and Mathematics (STEM) instruction using a dynamo-powered toy car. This design is referred to as a Local Instructional Theory (LIT) in teaching the linear equations in one variable material. The research method used is the method of design research, following the stages of preliminary design, teaching experiment, and retrospective analysis. The research subjects in the teaching experiment were grade VII students of a state junior high school in Bandung City. Data were collected from various sources, namely student worksheets, teacher and student observation sheets, documentation, interview, and video recording of the learning course. This study analyzes the validity of the research through a qualitative research perspective, and reliability refers to the quality of the survey itself. The research results described the performance of the LIT-based design for linear equations in one variable learning in STEM instruction in four meetings. The research was concluded with the generation of one local instructional theory that is valid, practical, and effective in guiding a set of instructional activities to build an understanding of the linear equations in one variable material through STEM instruction using a dynamo-powered toy car.